Effect of Dietary Fructus mume and Scutellaria baicalensis Georgi on the Fecal Microbiota and Its Correlation with Apparent Nutrient Digestibility in Weaned Piglets - Feng Zhang; Erhui Jin; Xiaodan Liu; Xu Ji; Hong Hu (Animals, 2022)
Traditional Chinese medicine (TCM) has long been demonstrated to exert a therapeutic effect on various diseases and has been used as a substitute for antibiotics in pig production. However, few studies have investigated the relationship between the intestinal microbiota and apparent nutrient digestibility when weaned piglet diets are supplemented with TCM. One hundred and sixty-two 25-day-old weaning piglets were housed in an environmentally controlled nursery facility and fed a basal diet (control group, n = 54) or a TCM complex (Fructus mume 1%, Scutellaria baicalensis Georgi 3%) (TCM group, n = 54), or a fermented diet with a complex of these two TCMs (F-TCM group, n = 54). Compared with the control group, in the TCM and F-TCM groups, the average daily gain (ADG) increased (p < 0.05), the F:G ratio and diarrhea rate decreased (p < 0.05), and the apparent digestibility of dry matter (DM) and ether extract (EE) of weaned piglets increased (p < 0.05). Bacteroidetes and Firmicutes were the predominant phyla, representing approximately 95% of all sequences. The abundance of four genera and 10 OTUs (belonging to Ruminococcaceae_UCG-014, Lachnoclostridium, Prevotellaceae_NK3B31 group, Prevotella_1) were negatively correlated with apparent EE digestibility (p < 0.05). The results suggest that weaned piglets fed with antibiotic-free diets supplemented with Fructus mume and Scutellaria baicalensis Georgi gained more weight and were healthier. When added to the diet, the complex of these two TCMs may have a direct impact on apparent EE digestibility by modifying the gut microbial composition, which favors the health of weaned piglets.